Behavior modification techniques for children with behavioral problems, silahis ng katarungan, division of city schools manila: an assessment - Ruiz, Maria Elena S. (Manila : National University, 2006)
This study revolved around the appraisal of the teacher-respondents on the effectiveness of the different behavior modification techniques, to lessen or eradicate the disruptive and undesirable behaviors of CBP. On the delimitation of the study it relied on the SPED teacher's answers to the questionnaire, guided interviews and the actual observations of the research.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.